ANALYSIS OF ROLE OF DECISION MAKING IN EFFECTIVENESS OF ELEMENTARY SCHOOL MANAGEMENT IN KUTAI KARTANEGARA - Nur Agus Salim (Borneo Educational Journal (Borju), 2019)
This study aims to analyze how the role of decision making on the effectiveness of primary schools in Kutai Kartanegara Regency. This research was conducted in 73 elementary schools in Kutai Kartanegara Regency. The method used in this study is a quantitative method with multiple regression analysis. The study sample was two hundred eighty two teachers from nine hundred and fifty-five populations. The results of this study explain that decision making plays a good role in the effectiveness of school management. Based on the results of this study, researchers concluded that the better the decision making by school management, the better the effectiveness of school management or it can be said that the effectiveness of good school management is realized with appropriate management decision-making.